(untitled) (UNED Research Journal, 2026)
Introduction: Organizational culture is an intangible element that directly influences employee behavior and determines the effectiveness of management systems; its quantification allows for the identification of opportunities for improvement. Objective: To design and validate an instrument for diagnosing and strengthening food safety culture in organizations within the food industry. Methods: We validated the instrument using the Delphi methodology with the participation of 21 experts from the food sector. Content validity was determined through the modified Lawshe method, reliability was assessed using Cronbach’s Alpha coefficient, and agreement was analyzed using Kendall’s W test. Finally, we applied the instrument in four food industry companies to verify its practical usefulness. Conclusion: We obtained a content validity index of 0.8 (40 accepted items), a Cronbach’s Alpha of 0.99, and an agreement coefficient of 0.47. Results showed variation in food safety culture levels among the four companies: very high in the sausage plant (84) and the verification entity (95); moderate in the fish processing plant (51), and very high in the meat distribution company (91). We conclude that the instrument is valid, reliable, and applicable for diagnosing and strengthening food safety culture in the food industry.